How groups reach agreement in risky choices: an experiment - Jingjing Zhang; Marco Casari (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2009)
This paper studies how groups resolve disagreement when they must reach unanimity after submitting individual proposals and exchanging text-form messages via a chat window in lottery choice experiments. We find that the majority proposal does not always prevail. The minority proposal prevails sometimes, especially when it is closer to risk neutrality. About one third of the groups disagrees after communication and would have got zero payoffs if disagreement remains after two more attempts without communication. In these groups, extrovert subjects are more likely to lead the group outcome than confused or conscientious subjects. Overall group choices are more coherent and closer to risk neutrality than individuals'. Checking the recorded messages, we find that the chat activity is intense, growing with the level of disagreement and aims at finding consensus. The amount and timing of chat messages help us to predict which choice prevails in the group.
Keywords: 330; Entscheidung unter Risiko; Gruppenentscheidung; Kooperatives Spiel